P119 T-bet+ B cells can serve as prognostic and therapeutic tools for human systemic lupus erythematosus - Sachinidis, Athanasios; Trachana, Maria; Taparkou, Anna; Keisaris, Sofoklis; Gavriilidis, George; Verginis, Panayotis; Adamichou, Christina; Boumpas, Dimitrios; Garyfallos, Alexandros (Lupus science & medicine, 2024)
ObjectiveThis study aims to clarify whether T-bet+ B cells, as well as the sub-populations of age-associated B cells/ABCs (CD19+CD21-CD11c+T-bet+) and double-negative B cells/DN (CD19+IgD-CD27-CXCR5-T-bet+), serve as prognostic and/or therapeutic tools for systemic lupus erythematosus (SLE) in humans.MethodsFlow cytometry was used to enumerate and immunophenotype T-bet+ B cells and ABCs/DN subsets, found in the peripheral blood of 10 healthy donors and 22 active SLE patients, in order to identify correlations between the cell populations and the clinical profiles of the subjects. Moreover, in order to evaluate the effects of traditional and modern pharmaceutical agents on T-bet+ B cells’ percentage, 24h-long primary cell cultures combined with in vitro pharmacological treatments (of 1h) were performed. Various concentrations of hydroxychloroquine, anifrolumab and fasudil (a ROCK kinase inhibitor) have been tested. Last, data derived from previous published single-cell RNA sequencing (scRNA-seq) studies, regarding 6 healthy donors and 11 active SLE patients, were used for a meta-analysis focusing on T-bet+ B cells, so as to allow characterization of the genes and pathways associated with the biology of this specific transcription factor.ResultsT-bet+ B cells, as well as ABCs and DN, displayed a statistical significant expansion in the patients, compared to the healthy donors. Interestingly, percentages of T-bet+ B cells and DN B cells positively correlated with the SLEDAI scores of the patients. Cell culture experiments conducted, revealed that all three drugs tested are capable of depleting T-bet+ B cells (while leaving unaffected the total numbers of lymphocytes, T cells and B cells, respectively). According to bioinformatics analyses, moreover, T-bet in B cells seems to affiliate with transcription factors that play a role in germinal centers’ development (such as BCL6 and IRF8) in lupus patients, while in healthy individuals it affiliates with JUN. Additionally, an analysis regarding intracellular communications amongst B cell populations revealed that the transcription factor of interest is closely associated with inflammatory secretome during lupus.ConclusionsT-bet+ B cells associate with SLEDAI, thus can serve as a prognostic biomarker of lupus severity. Furthermore, these cells promote disease pathogenesis and can be targeted for therapeutic interventions.AcknowledgementsThe research work is supported by the Hellenic Foundation for Research and Innovation (HFRI) under the 3rd Call for HFRI PhD Fellowships (Fellowship Number: 5148, Awarded to AS). Moreover, the study is funded (partially) by the Hellenic Society of Rheumatology & Professional Association of Rheumatologists (Protocol Number: 1064, Research Grant awarded to CA)